(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article examines the theoretical and methodological foundations of organizing spiritual and educational activities in preschool educational institutions based on national values. The study analyzes the role of folk pedagogy, national traditions, customs, and cultural heritage in the formation of spiritual awareness, moral qualities, and national identity in preschool children. The methodology for designing and implementing spiritual-educational activities is presented, and practical recommendations for educators are provided.